2005
DOI: 10.1086/428910
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Holoendemic Malaria Results in Elevated Epstein‐Barr Virus Loads in Children

Abstract: Perennial and intense malaria transmission (holoendemic malaria) and Epstein-Barr virus (EBV) infection are 2 cofactors in the pathogenesis of endemic Burkitt lymphoma (eBL). In the present study, we compared EBV loads in children living in 2 regions of Kenya with differing malaria transmission intensities: Kisumu District, where malaria transmission is holoendemic, and Nandi District, where malaria transmission is sporadic. For comparison, blood samples were also obtained from US adults, Kenyan adults, and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
196
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 190 publications
(224 citation statements)
references
References 31 publications
18
196
2
2
Order By: Relevance
“…One important eBL co-factor, Epstein-Barr virus infection, is evenly distributed in the population and infection occurs early in childhood. 21,22 Our consistent findings, therefore, may imply clustering of other environmental or socio-cultural eBL co-factors, although potential reporting bias must also be assessed. Neither high-risk cluster included administrative units in Siaya District, as initially hypothesized.…”
Section: Spatial Clusteringmentioning
confidence: 82%
“…One important eBL co-factor, Epstein-Barr virus infection, is evenly distributed in the population and infection occurs early in childhood. 21,22 Our consistent findings, therefore, may imply clustering of other environmental or socio-cultural eBL co-factors, although potential reporting bias must also be assessed. Neither high-risk cluster included administrative units in Siaya District, as initially hypothesized.…”
Section: Spatial Clusteringmentioning
confidence: 82%
“…Although age differed between the groups, with the controls being slightly older than the cases, both groups were within the age range of children at risk of developing eBL (i.e., 5-9 years of age). 32 There were several limitations to this study. Because of this study being conducted in a limited-resource setting, diagnosis was not confirmed by immunohistochemistry; therefore, it is possible but highly improbable that BL patients may have been misclassified.…”
Section: Discussionmentioning
confidence: 94%
“…A distinct possibility exists for genetic variation that alters the balance between antiinflammatory and proinflammatory cytokines to contribute to the immunologic dysregulation over EBV observed in eBL. [32][33][34] IL-6 and IL-10 are two cytokines that have been implicated in the pathogenesis and progression of other lymphoproliferative disorders. 14,35,36 We hypothesized that these cytokines could potentially provide a permissive milieu for eBL oncogenesis, and therefore, patients with eBL might be more likely to possess genotypes that predispose them to higher levels of inducible IL-6 and IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation that long-term persistence of a murine gammaherpesvirus is age-dependent, as is the development of an IM-like syndrome, suggests that a greater understanding of persistence of gammaherpesviruses in children is needed. Indeed, we have reported the ready detection of EBV DNA and high viral loads in peripheral blood in children under the age of four living in Kenya (Moormann et al, 2005). Whether early age of infection leads to higher viral persistence in mucosal sites in children remains to be determined, but it is relevant to note that endemic Burkitt's lymphoma only affects children and that the presentation of tumours is primarily in the jaw (de-The, 1977).…”
Section: Discussionmentioning
confidence: 99%